FRI0100 Multi-omics analysis identifies a gene signature associated with the clinical response to anti-tnf therapy in rheumatoid arthritis. (12th June 2018) - Aterido, A.; Tornero, J.; Blanco, F.; Fernández-Gutiérrez, B.; González, A.; Cañete, J.D.; Maymó, J.; Alperi-López, M.; Olivé, À.; Corominas, H.; Martínez-Taboada, V.; González, I.; et al.
Abstract : Background: Tumour Necrosis Factor (TNF) inhibitors have improved the management of many patients with rheumatoid arthritis (RA). However, 30% of anti-TNF treated patients do not show a significant clinical improvement. To date, little is known on the biological mechanisms underlying the differential response to anti-TNF agents. Objectives: We sought to identify genetic variation associated with the anti-TNF response in RA using a sequential multi-omics approach. Methods: First, we aimed to identify gene coexpression modules (GCMs) associated with anti-TNF response. For this objective, we extracted the RNA from synovial biopsies of 13 RA patients starting anti-TNF therapy and determined the expression profiles using Illumina microarrays. GCMs were identified using the WGCNA approach. The association between GCMs and anti-TNF response was performed using the eigengene of each GCM. Clinical response was defined using the EULAR criteria at week 14. To analyse the association of GCMs with anti-TNF response at the genetic level, we used 348 anti-TNF treated RA patients from Spain. The statistical analysis was performed using GWAS data and the set-based test in PLINK. The GCMs that were significantly associated with anti-TNF response were subsequently tested for validation in an independent cohort of 2706 anti-TNF treated RA patients. The functional implication of the validated GCMs was studied via pathway and cell type epigenetic enrichment analyses. Results: We identified 148 GCMs in the RA synovium. From these, 15 GCMs were found to be associated with anti-TNF response (p<0.05). At the genetic level, we found two of the 15 GCMs to be associated with the adalimumab (ADL) and infliximab response (p<0.05) in the Spain cohort. In the independent cohort, we replicated the association of the GCM associated with ADL response (p=0.01). The validated GCM was found to be enriched in genes that participate in the nucleotides metabolism (p=2.41e-5). The epigenetic analysis revealed that ADL-associated variants are enriched in epigenetic marks from immune cell types like Tregs (p=0.04). Conclusions: Our study shows the existence of a drug-specific genetic basis for the anti-TNF response. Therefore, this molecular diversity should be considered for biomarker research in RA. Disclosure of Interest: None declared